Primigravida with diffuse uterine leiomyomatosis and IUGR necessitating a caesarean section and hysterectomy - Layla Hassan; Candace P Beoku-Betts; Oluseye A Oyawoye (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
Diffuse uterine leiomyomatosis is uncommon and often associated with infertility. To date, few successful pregnancies have been published within the context of the condition. Of the known cases, all but one have occurred after medical, radiological or surgical management. Here, we report a case of diffuse uterine leiomyomatosis in a 39 year-old diagnosed intrapartum. Caesarean hysterectomy was performed at 30+5 week gestation due to massive peripartum haemorrhage secondary to diffuse nodular leiomyomatosis. All her antenatal scans reported multiple uterine fibroids and diffuse leiomyomatosis was not suspected until the time of caesarean section. At 6320 gm this is the largest sized uterine tissue so far published.